Multi-wavelength, spatially resolved modelling of HD 48682's debris disc. Issue 1 (8th July 2020) - Hengst, S; Marshall, J P; Horner, J; Marsden, S C
ABSTRACT: Asteroids and comets (planetesimals) are created in gas- and dust-rich protoplanetary discs. The presence of these planetesimals around main-sequence stars is usually inferred from the detection of excess continuum emission at infrared wavelengths from dust grains produced by destructive processes within these discs. Modelling of the disc structure and dust grain properties for those discs is often hindered by the absence of any meaningful constraint on the location and spatial extent of the disc. Multi-wavelength, spatially resolved imaging is thus invaluable in refining the interpretation of these systems. Observations of HD 48682 at far-infrared ( Spitzer, Herschel ) and sub-millimetre (JCMT, SMA) wavelengths indicated the presence of an extended, cold debris disc with a blackbody temperature of 57.9 ± 0.7 K. Here, we combined these data to perform a comprehensive study of the disc architecture and its implications for the dust grain properties. The deconvolved images revealed a cold debris belt, verified by combining a 3D radiative transfer dust continuum model with image analysis to replicate the structure using a single, axisymmetric annulus. A Markov chain Monte Carlo analysis calculated the maximum likelihood of HD48682's disc radius ($R_{\rm disc} = 89^{+17}_{-20}~$ au), fractional width ($Δ R_{\rm disc} = 0.41^{+0.27}_{-0.20}$ ), position angle ($θ = 66{_{.}^{°}} 3^{+4.5}_{-4.9}$ ), and inclination ($φ = 112{_{.}^{°}} 5^{+4.2}_{-4.2}$ ). HD 48682 has been revealed to host a collisionally active, broad disc whose emission is dominated by small dust grains, s min ∼ 0.6 μ m, and a size distribution exponent of 3.60 ± 0.02.